Pengaruh Harga dan Kualitas Produk Terhadap Volume Penjualan Selada Hijau organik - khoirudin, Mufti; ., Istanto; Wahyuningsih, Sri; Widianti, Aniya (CV.ITTC INDONESIA, 2025)
Lettuce (Lactuca sativa L.) is a horticultural commodity with high economic and nutritional value. This quantitative study analyzes the influence of price and product quality on the sales volume of organic green lettuce in the Bangkit Merbabu Farmers Group, Batur Village, Getasan District, Semarang Regency. The research was conducted from May to June 2025 using a case study method with purposive sampling. A total of 33 respondents, consisting of group members and administrators, were selected. Primary data were obtained through questionnaires, interviews, and observations, while secondary data came from literature and statistical reports. The data were analyzed using multiple linear regression with F-test, T-test, and coefficient of determination (R²). The results show that price and product quality simultaneously and partially have a significant effect on sales volume. The determination coefficient (R²) value of 82.3% indicates that variations in price and product quality explain most of the changes in sales volume, while 17.7% is influenced by other factors not examined. The findings highlight that competitive pricing strategies and consistent product quality are essential to strengthen market competitiveness and increase sales of organic green lettuce.